Analisis Sastra Siber Puisi Nyanyian Angsa Karya W.S. Rendra dengan menggunakan Pendekatan Objektif (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The poem titled "Nyanyian Angsa" by W.S. Rendra is one of his works rich in meaning, especially in a social context. In the digital era, revisiting this work through cyber literature offers a new perspective that is more accessible to readers. This study aims to explore how the intrinsic elements of the poem can be objectively analyzed within the digital media domain. The objective of this research is to reveal the structure and intrinsic components that shape "Nyanyian Angsa", enabling readers to gain a deeper understanding of the poem's overall meaning. This study employs a descriptive method with an objective approach, focusing on the poem's text itself as the main data source, with reference to its intrinsic literary elements. The findings reveal that "Nyanyian Angsa" demonstrates intertextuality with the story of Maria Zaitun, previously published as a novel by Joko Santoso. The poem also forms a strong yet free narrative structure. The analysis shows that aesthetic value and message remain intact even when presented in digital form. This affirms that cyber literature can serve as an effective medium to revive and reintroduce classical literary works.